Widening the perspective in greenhouse gas emissions accounting: The way forward for supporting climate and energy policies at municipal level. (1st March 2018) - Martire, Salvatore; Mirabella, Nadia; Sala, Serenella
Abstract: The transition towards low-carbon economy requires a number of specific actions by a multiplicity of actors in order to reduce greenhouse gas (GHG) emissions, entailing energy efficiency, production of energy from renewable resources as well as the diffusion of more sustainable production and consumption patterns. Among the actors, local authorities can play a leading role for climate action. However, properly accounting for GHG emissions at local scale and identifying actions for GHG reduction are still an open challenge in many contexts. In this paper, we propose a method for GHG emissions accounting to support the identification of proper actions to achieve GHG reduction targets. The method widens the classical production-based approach to accounting, by proposing an extension of the accounting to three main areas: waste management and recycling, consumption patterns, and local land management. Life cycle thinking is applied as methodological basis for such extension. To illustrate the benefit of the proposed approach, the method has been applied to 16 municipalities (in Northern Italy), which were signatories of the Covenant of Mayors (CoM) initiative. CoM is a European initiative by which local authorities voluntarily commit to reduce their GHG emissions through the implementation of Sustainable Energy Action Plans. A comparison of the emission profile of the different municipalities helps identifying common patterns and local peculiarities to be addressed to achieve the reduction target. For the analysed case studies, the biggest contribution to GHG emissions comes from the consumption of the natural gas and electricity by the household sector. Emissions from waste generation play a minor role in the selected case studies. However, the inclusion of avoided emissions coming from waste recycling highlights the reduction potential if an appropriate waste management system is in place. Consumption patterns, as well, may play a relevant role. For example, assessing GHG emissions related to food consumption on top of those due to other drivers, the total municipal emissions change by increasing for an average of 22.6% for the selected case studies. Moreover, local land use planning and management should be included in the assessment, being crucial not only for the emissions uptake but also for climate mitigation and adaptation. The proposed approach to GHG accounting, including consumption-based aspects, may help identifying a wider set of climate actions to be implemented by local authorities to reduce environmental burdens. Highlights: Local authorities play a key role to reach EU's energy and climate targets. An extended GHG emissions accounting method is proposed to support local low-carbon policies. The method was tested in 16 municipalities in Italy signatories of the Covenant of Mayors initiative. Consumption of goods, waste recycling, and local land management may be included in the accounting. Consumption-based approaches enlarge the focus for defining action towards reducing GHG.